Analisis Pengaruh Pemberian Kredit Usaha Rakyat (KUR) PT Pegadaian terhadap Peningkatan Pendapatan Nasabah - Fahrudin, Fahrudin; Qomariyah, Nurul Ulfa; Febriana, Indah Karima; Fitriyah, Fitriyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study analyzes the impact of the Credit for People’s Business (KUR) provided by PT Pegadaian on increasing the income of micro, small, and medium enterprises (MSMEs). KUR aims to provide working capital with low-interest rates to improve the welfare of customers. The study aims to identify the effects of KUR on customers' income, the factors supporting and hindering the effectiveness of the program, and the income differences before and after receiving KUR. The research uses a qualitative approach with a descriptive design, collecting data through observation, interviews, and documentation with purposive sampling technique. The results show that KUR has increased customers' income by 20-40%. The funds are used to expand business scale and reach broader markets. Key supporting factors include low interest rates and ease of access, while main challenges include low financial literacy and limited access in remote areas. The study concludes that KUR effectively increases income, but improvements in financial literacy and infrastructure are needed for broader impact.